Assessment of the Feasibility of Therapeutic Equivalence Studies - D. V. Goryachev; N. E. Uvarova (Регуляторные исследования и экспертиза лекарственных средств, 2019)
The introduction of the «therapeutic equivalence» concept into the Russian legislation is critical for evaluation of medicines interchangeability and for recognising them as generics. It is stipulated by the legislation that therapeutic equivalence has to be evaluated using a special instrument — «therapeutic equivalence study». The aim of this work was to analyse the validity of considering a therapeutic equivalence study as the only study that allows for confirmation of therapeutic equivalence of medicines. The term «therapeutic equivalence» has been adopted by the leading world regulators, but there is no clear concept of what is a therapeutic equivalence clinical study. The key distinctive features of the foreign approach, as compared to the Russian one, are comparison of medicines with one active pharmaceutical ingredient, and additional conditions for the establishment of therapeutic equivalence. The clinical trial methodology, which is based on the use of statistical analysis methods, also imposes constraints on evaluation of «similarity» of properties, efficacy and safety of medicines in a single study. Hence, there are several reasons why the results of comparative clinical trials can not be used as a sole basis for the establishment of therapeutic equivalence. These results have to be substantiated by confirmation of comparable composition and pharmacokinetic parameters of medicines in order for them to be considered therapeutically equivalent. This does not contradict the existing regulatory framework and is consistent with the current scientific methodology for conducting clinical trials.